Effects of Explicit and Generative Instructional Strategies on Senior Secondary School Students’ Learning Outcomes in Summary Writing in Ibadan Metropolis, Nigeria (2014)
Reports from public examination bodies reveal that students’ performance in English Language is poor. This has been traced to perceived wrong instructional strategies adopted by most teachers of English language. Literature has suggested the adoption of explicit and generative instructional strategies that address the deficiencies. However, there is a dearth of empirical research on the effectiveness of the two strategies on summary writing among Senior Secondary School (SSS) students, particularly in Ibadan metropolis. This study, therefore, examined the effects of explicit and generative instructional strategies on students’ achievement in and attitude to summary writing in Ibadan Metropolis. The moderating effect of cognitive style and gender were equally examined. The study adopted pretest-posttest, control group quasi-experimental design with a 3x2x2 factorial matrix. Participants were 200 SSS II students from six purposively selected intact classes of six public secondary schools in Ibadan metropolis. The students were assigned to explicit instructional strategy (75), generative instructional strategy (65) and control (60) groups. Treatment lasted twelve weeks. Seven instruments were used: Summary Writing Achievement Test (r=0.81), Attitude to Summary Writing Questionnaire (r=0.78), Cognitive Style Inventory (r=0.74), Instructional Guides on Explicit, Generative and Conventional Instructional strategies and Teachers’ Evaluation Sheet. Data were analysed using Analysis of Covariance at 0.05 level of significance and Scheffe post hoc test was also performed. Treatment had significant main effect on students’ achievement (F(2,187)= 12.21) and attitude (F(2,187) = 9.23) to summary writing. Participants in the explicit instructional strategy group obtained the highest achievement score (x = 16.82,η2 =.47) followed by the generative instructional strategy (x = 14.65,η2= .36) and control (x = 12.91,η2=.19). Also, participants in the explicit instructional strategy group obtained the highest attitude score (x = 38.87,η2=.41) followed by the generative instructional strategy (x = 37.45,η2=.35) and control (x = 32.41,η2=.22). Cognitive styles had significant main effect on students’ achievement in summary writing (F(2,187) = 66.60) and none on their attitude. Effect of global cognitive style was lower in students’ achievement (x = 11.19,η2= .35) than in analytic cognitive style (x = 19.09,η2=.47). Also, effect of global cognitive style was slightly higher in students’ attitude (x = 36.48,η2=.49) than in analytic cognitive style (x = 36.46,η2=.48). Gender had no significant main effect on students’ achievement and attitude to summary writing. Effect of gender was lower in male students’ achievement (x = 14.73,η2= .35) than in female students’ (x = 15.22,η2= .38). Also, effect of gender was slightly higher in males’ attitude (x = 36.78,η2= .41) than in females’ (x = 36.13,η2= .40). The two-way and three-way interaction effects were not significant on achievement and attitude. Explicit and generative instructional strategies improved students’ learning outcomes in summary writing. Hence, English language teachers should employ these strategies to improve secondary school students’ achievement in and attitude to summary writing.